The Legal Framework and Governance Challenges of Sovereign Wealth Funds in Indonesia: A Comparative Study of Danantara and the Indonesia Investment Authority - Deva Nabilah; Benny Sultan; Deva Yulinda; Muhammad Izzi (Fakultas Syariah dan Hukum UIN Raden Fatah Palembang, 2025)
Indonesia is undergoing a major transformation in its sovereign investment management through the establishment of two key entities: the Indonesia Investment Authority (INA) and Danantara. While both were established with the aim of strengthening long-term economic performance and increasing public and international investment, various challenges related to good governance have emerged—such as political interference, lack of transparency, potential conflicts of interest, and weak legal oversight. This study aims to conduct a comparative analysis of the institutional structures and legal frameworks of INA and Danantara, and to evaluate the extent to which their practices adopt the principles of good governance (including accountability, transparency, effectiveness, the rule of law, and public participation). The research method is a normative qualitative approach with juridical-documentary studies and interviews with relevant stakeholders, as well as comparative analysis between institutions. The research results are expected to identify gaps between regulations and field practices, highlight key risks in the management of sovereign wealth funds in Indonesia, and provide policy recommendations to strengthen accountability and oversight mechanisms, increase transparency, and strengthen the independence of sovereign investment institutions. This research contributes to the literature on SWF governance and state administration and provides a policy foundation for sustainable institutional improvement.